Enrichment in Architecture An Explorative Study ofthe Formal Enrichment Achieved by Contrast - alâ€ DabbaghAsma Hasan (Iraqi Journal of Architecture and Planning, 2009)
Architectural literatures and practices presented the concept of Enrichment as one of the solutions for the problems of Modemism. The importance of this concept emerges due to its relation with other phenomena like visual complexity and ambiguity. Enrichment is a product character and a strategy to its creation. This product possess abundance and detail in the visual tools causing the meaning enrichment and its readiness for multi interpretations. This concept is present in to two levels; the first, formal and includes complexity and riddles, while the second is moral which includes the multiinterpretations. These sub-concepts cover many tools to achieve it like redundance, contrast, formal transformations, slight contrast within a strong order and an ambiguous meaning. This research dealt with contrast in its practical study. It defined this tool with its major and secondary variables. Also, this study tried to explore the possible characteristics and values generating contrast by applying it on two architectural projects. The results showed new characteristics and values for contrast which were not mentioned by previous literatures. In addition, the conclusions showed that the architects depend on contrast in forms reference which in tum affect the total and peripheral characteristics ofthese forms. The latter conclusion supports the contexts of previous literatures.